Petrogenesis of the NWA 7320 enriched martian gabbroic shergottite: Insight into the martian crust. (1st May 2017) - Udry, Arya; Howarth, Geoffrey H.; Lapen, Thomas J.; Righter, Minako
Abstract: Northwest Africa (NWA) 7320 is classified as a gabbroic shergottite, the second to be recognized in the martian meteorite record. This interpretation is based on: (1) the calculated bulk-rock rare earth element (REE) concentrations, which show the highest Eu positive anomaly (Eu/Eu ∗  = 2.2) of all the shergottites, reflecting accumulation of plagioclase; and (2) the highest modal abundance of maskelynitized plagioclase (50 mod.%) compared to the other shergottites. The three-phase symplectite (fayalite + hedenbergite + silica) is present in NWA 7320 and formed as a result of the breakdown of metastable pyroxene/pyroxenoid margins on coarse-grained pyroxenes. The latter is indicative of metastable overgrowths on pyroxene cores during the final stages of crystallization, followed by relatively slow cooling at subsolidus conditions. The NWA 7320 parental melt originated from an incompatible trace element enriched and oxidized (∼FMQ) source as indicated by Sm–Nd, Lu–Hf isotope systematics, ilmenite-titanomagnetite pairs, the partition coefficient of Cr in pyroxene, and merrillite REE compositions. The Ti/Al ratio of pyroxene in NWA 7320 indicates an initial crystallization depth of 30–70 km ( P  = 4–9 kbar). However, the largest impact craters on Mars are <8 km in depth, indicating that NWA 7320 could not have been ejected from this depth and must have had a polybaric formation history. We suggest that the pyroxene phenocrysts began to crystallize at depth, but were entrained as antecrysts in a basaltic magma ascending to shallower levels in the martian crust. In addition, plagioclase likely crystallized during magma ascent, followed by subsequent accumulation in a shallow magma intrusion or sill, resulting in the gabbroic texture. Furthermore, the similarity in the radiogenic isotope composition of NWA 7320 to that of Los Angeles and NWA 856 suggest that these meteorites were linked to common volcanic system on Mars.